The gas-transport enterprises in system of the gas industry (Путеводитель предпринимателя, 2020)
The article is devoted to a problematic of development of the gas-transport enterprises during the postcrisis period. The author specifies a place gas-transport the enterprises in the gas industry and a role in market economy of the country. The factors constraining development of the gas-transport enterprises are allocated.